Bilateral vocal cord paralysis in a patient with myasthenia gravis. Issue 1 (15th May 2013) - Zhou, Guojun; Wu, Min; Xia, WeiSheng
Summary: A 65‐yr old female developed bilateral vocal cord paralysis following thoracoscopy and pulmonary resection. Surgery, which was performed using a thoracoscope and with lung separation techniques, proceeded without complication. She was transferred to the ICU after surgery and extubated on the third postoperative day when she complained of persistent severe hoarseness and dysphasia. She was subsequently diagnosed with myasthenia gravis and bilateral vocal cord paralysis due to bulbar muscle fatigue. Treatment was with prednisolone and pyridostigmine bromide. Oesophageal function recovered on the twenty‐second day and she regained her normal voice four weeks later. We describe this rare cause of postoperative hoarseness and discuss the causes.